EDUCATION OF MEMBERS OF TRANSPORT SERVICES OF TSARIST RUSSIA IN THE 1830S. ADMISSION AND EXAMINATION OF STUDENTS OF THE SAINT PETERSBURG INSTITUTE OF CORPS OF ENGINEERS OF ROADS OF COMMUNICATION - Marek RUTKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport, 2019)
This paper focuses on the phenomenon of the strongly complicated process of education of cadets and officers of tsarist transportation services corps during the 1830s of the 19th century. While primarily commencing this short study with introduction and changes in the didactic process occurring in Saint Petersburg Institute of Corps of Engineers of Roads of Communication at the early stages of its development, the main scope of the research was to describe: a) changes and restriction in the accessibility to the very process of education given in this Institute, b) the alteration in the formal entry and most of all scientific requirements. c) the outcome and circumstances of final examinations, all happening during the third decade of 19th century.